STUDENTS’ PERCEPTION TOWARDS THE IMPLEMENTATION OF CURRICULUM USED IN SMP PANGUDI LUHUR MOYUDAN - Dian Palupi; Jannatul Laily Novia Bahari (Lembaga Pengembangan Kinerja Dosen, 2022)
As one of the education elements, curriculum has an important role as a guide to succeed the educational system. It is formed to achieve the goals and objectives of educational desires. Thus, the government, teachers, administers, and educators need to consider the implementation of the appropriate and suitable curriculum in order to achieve the educational goals. This study aims to investigate the students’ perception towards the implementation of current curriculum used in SMP Pangudi Luhur Moyudan. It is a qualitative study involving 61 JHS students. Those students represent the high-achieved, the middle-achieved, and the low-achieved students. The data were collected through interviews and analyzed using the analysis model of Miles, Huberman, and Saldana, following the steps of data condensation, data categorization, data display, data interpretation, and conclusion drawing and verification. The findings show that the students of SMP Pangudi Luhur Moyudan have positive perception towards the implementation of current curriculum in their English class, which is 2013 Curriculum.